IMPORTANCE OF SPORTS PSYCHOLOGY AND IMPORTANCE OF SPORTS IN DAILY ROUTINE - Dr.Riya N.Vaghela; Dr. Drashti Patel (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
In today’s sedentary lifestyle, where technology dominates our daily activities, the significance of sports and exercise in our routines cannot be overstated. Engaging in regular physical activity offers numerous benefits for both physical and mental well-being. This article aims to highlight the importance of sports and exercise in daily routines, supported by relevant references.